2022
DOI: 10.1177/08997640221110211
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Regional Determinants of the Emergence of Social Enterprises in South Korea: An Entrepreneurial Ecosystem Perspective

Abstract: South Korea has experienced a rapid increase in the emergence of social enterprises that aim to address various social problems. However, little is known about the conditions that can affect the emergence of social enterprises at the regional level. This study examined the regional factors that influence the establishment of social enterprises using a panel dataset of observations on 17 metropolitan cities and provinces in South Korea from 2012 to 2019. The appearance of social enterprises in regional entrepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…Nonprofits respond to historical and social contexts (Woo & Jung, 2023), and research on nonprofit density has revealed differences in the capacity of communities to support nonprofits, as nonprofit density may respond to poverty and the racial composition of the neighborhood (Joassart-Marcelli & Wolch, 2003; McDonnell et al, 2020; Wo, 2018). Yet, neighborhood conditions may have ramifications for the financial health of organizations as well.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonprofits respond to historical and social contexts (Woo & Jung, 2023), and research on nonprofit density has revealed differences in the capacity of communities to support nonprofits, as nonprofit density may respond to poverty and the racial composition of the neighborhood (Joassart-Marcelli & Wolch, 2003; McDonnell et al, 2020; Wo, 2018). Yet, neighborhood conditions may have ramifications for the financial health of organizations as well.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of nonprofit density using small geographic units, such as U.S. census tracts or local Authorities in the United Kingdom, show density is positively related over time (McDonnell et al, 2020; Wo, 2018). While organizations enter markets by selecting locations where they may be successful in meeting their mission (Woo & Jung, 2023), locations differ dramatically with respect to organizational density, norms of behavior, governance strategies, reputation, and resource abundance (Lomi, 1995). Consequently, the location of the organization has implications for its viability, as well as their ability to develop relationships, and become embedded to obtain legitimacy and access resources (Greve, 2002; Swaminathan, 1996).…”
Section: Carrying Capacity and Theories Of Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the methodologies used by studies, most geographical research on social enterprises have used qualitative methods, with some exceptions in studies that take a regional perspective. In these instances, studies have predominantly used existing survey data and registers of social enterprises (Woo and Jung, 2023). In terms of theoretical perspectives, some studies are based on economic geography theories such as agglomeration and cluster theory (e.g.…”
Section: Geographicalmentioning
confidence: 99%
“…In addition to start-ups and scale-ups (or high-growth entrepreneurship), recent research has broadened the range of entrepreneurial outputs from EEs. Examples include social and sustainability-oriented entrepreneurship (Audretsch, Eichler & Schwarz, 2022;Tiba, Van Rijnsoever & Hekkert, 2021;Woo & Jung, 2022), female entrepreneurship at the regional level (Berger & Kuckertz, 2016;Welsh et al, 2023), frugal and informal entrepreneurship (Igwe et al, 2020), entrepreneurship in the creative industries (Wang & Richardson, 2021), and the creation of knowledge intensive business services (Horváth & Rabetino, 2019).…”
Section: Entrepreneurial Ecosystems and Entrepreneurial Outputsmentioning
confidence: 99%